Assessing Fiscal Sustainability in Theory and Practice - Chalk, Nigel (IMF Working Papers; Working Paper ;, 2000)
The main purpose of this paper is to provide an overview of approaches to assessing fiscal sustainability. It summarizes the general analytical background, focusing on the present value budget constraint, which is the benchmark against which solvency is determined, tests of sustainability (including sustainability indicators), and sustainability and uncertainty. The paper then looks at the way in which fiscal sustainability has been assessed in different types of IMF work. Finally the link between fiscal and external sustainability is discussed.